TREND PENJUALAN PROPERTI DI BANDUNG: Latest Property Sales Trends in Bandung - Wulandari, Fransisca Wuri (LPPM Politeknik Pajajaran ICB Bandung, 2025)
This journal comprehensively analyzes property sales trends in Bandung, reviewing market dynamics from 2023 to mid-2025. Using a combination of qualitative and quantitative research methods, we identify key factors influencing market movements, including changes in consumer preferences, the impact of new infrastructure, government policies, and macroeconomic conditions. The research results show a significant shift in market demand, with vertical properties such as apartments and integrated residential developments becoming the primary choice, particularly in strategic locations near business and educational centers. Meanwhile, landed property trends are also shifting, with consumer interest shifting to suburban areas that offer a balance between accessibility, convenience, and affordability. This paper also identifies key challenges facing developers and buyers, such as fluctuating mortgage interest rates and increasingly limited land availability. We conclude that the Bandung property market remains resilient and offers promising investment potential for investors and buyers who are diligent in adapting to evolving trends.